VD_FINDINFO HC / 2016 / 1108 vom 13. Oktober 2016 - VD Tribunal cantonal (2016)
PROVISIONCOMMISSION, DÉCOMPTESENS GÉNÉRAL, OBLIGATION DE RENSEIGNER, INTERPRÉTATIONSENS GÉNÉRAL | 18 al. 1 CO, 322b CO, 322c CO, 349a al. 2 CO, 106 al. 2 CPC (CH)